A produção do gênero monografia em discursos de professores e alunos do curso de letras - Pereira, Crígina Cibelle (2012)
A current worry in the teaching process at the university these days is text production process and genres produced there, especially those kind of writing that is concerned to course conclusion such as monograph, dissertation and thesis. From this perspective and considering our aims at understanding discursive process involved in the production of monograph genre at the university we want to analyze teachers and students discourses about the productive process of monograph in Letras Course, considering the guide, writing and specific aspects of that genre. To get the aims, we took as background theory the studies by Bakhtin linked to Utterance Linguistics with foundation concepts in Discourse Text Analysis by Adam (2010), and finally the studies developed about text production at college. This way, this work is based on a qualitative research and in data ethnographic procedures, they are: the observation in locus, as well as the application of questionnaires with opened questions to ten students and six teachers from Letras Course. The discourse analysis from the subjects reveal us that: i) the monograph production and the guidance are form of act by language, that need take into account in its development: students free chose as a principle in writing monograph, as well as a wide involvement between the teacher and the student in a sense to turn the writing better, among other aspects; (ii) there is a need to articulate monograph project and the text produced, considering that the guide process comes from a project written before; (iii) there are a number of role to discourses by teachers and students to the function of student and guide teacher, in a way that both can see the same assumptions in teachers and students discourses; (iv) teacher s and students discourses show that they assume the utterance responsibilities by the content of utterances proposed, they also show the voice from methodology guidebooks to monograph texts. So, we conclude that this research has some contributions to teach writing production at the university, especially to monograph in the ending of the courses. It can also be helpful in developing research in this area, mainly at the question about guide final works at college